ATP- and Adenosine-Mediated Signaling in the Central Nervous System: Synaptic Purinoceptors: the Stage for ATP to Play Its "Dual-Role" - Fusao Kato; Masahito Kawamura; Eiji Shigetomi; Jun-ichi Tanaka; Kazuhide Inoue (Elsevier, 2004)
The studies aiming to understand the function of purinoceptors in the central nervous system (CNS), which has been explored mostly in isolated and cultured cell systems, are now at the stage of identifying their physiological and pathophysiological significance in the native organs, tissues, and whole animals. The results of our recent studies made in brain slice preparations are not in full accordance with what have been demonstrated in isolated cells, mostly due to strong interplay between ATP receptors, adenosine receptors, and ecto-nucleotidases. This suggests that these proteins form coordinated regulation systems in the native tissue, controlling the local network behaviors through regulating the balance between the effects of ATP and adenosine on synaptic transmissions. We propose that this tripartite regulation system by extracellular purines may be an important target of CNS drugs. Keywords:: nucleus tractus solitarii, synaptic transmission, hippocampus, postsynaptic current, transmitter release